Standalone photovoltaic (PV) systems for disaster relief and remote areas - Qazi, Salahuddin, 1938- (Elsevier, 2016)
Standalone Photovoltaic (PV) Systems for Disaster Relief and Remote Areas explores the increased demand for energy, including clean energy alternatives and the ways that solar energy is fast becoming a vital source for meeting peak demand, a solution for energy demand in disaster and remote areas, and a viable source to meet emerging energy security needs. The book provides a detailed overview of PV systems and applications for disaster and remote areas, and includes a guide on how to provide electricity during outages, along with important discussions on the need for increasing the resilience of the grid. The differences and requirements for standalone, mobile, and portable PV systems are discussed, along with how systems can be deployed, transported, and used in remote areas. In addition, the book discusses the use of solar PV systems to create environmentally friendly power systems for remote communities that can be operated independently, also comparing the costs, emissions, and practical applications of other technologies. Types of natural disasters, their effect on peoples' lives, on world economy, impact on electric grid and costs of power outages Energy Needs in the aftermath of disasters and remote areas both in developed and developing Countries, including how PV systems can provide electricity affordably, with resilience and reducing grid impact by way of community solar and solar microgrid Detailed description of the types and components of standalone photovoltaic systems, modeling and simulation and performance analysis New initiatives, programs and case studies for providing solar-generated electricity to low-income people both in the United States and the developing world at low cost Examples of assembling one's own PV module and dye-sensitized solar cells, results, databases and industry standards.
Includes index.
Keywords: Photovoltaic power systems.; elektronické knihy; electronic books